2012
DOI: 10.1016/j.foodchem.2011.05.111
|View full text |Cite
|
Sign up to set email alerts
|

A rheological characterisation of mashed potatoes enriched with soy protein isolate

Abstract: The effect of the addition of soy protein isolate (SPI) (0, 15, 30, 45 and 60 g kg-1) on viscoelastic properties, large deformation measurements and microstructure of fresh (FM) and frozen/thawed (F/TM) mashed potatoes was investigated. Rheological data showed weak gel behaviour for both FM and F/TM potatoes without and with added SPI together with a significant decrease of system viscoelasticity (G' and G") with increasing SPI volume fraction, primarily attributed to the no interaction between the amylose/amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…All the measured rheological parameters (viscosity, thixotropy, yield stress, and viscoelastic behavior) on the formulations without agar significantly increased with rising the soy concentration from 3% to 5%, but from 5% to 7% they had no significant differences, which can be explained by insufficient water in the formulation caused by the high concentration of solids. This phenomenon has been previously reported, with a decrease in thickening for the highest concentrations of added soy protein (Alvarez et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…All the measured rheological parameters (viscosity, thixotropy, yield stress, and viscoelastic behavior) on the formulations without agar significantly increased with rising the soy concentration from 3% to 5%, but from 5% to 7% they had no significant differences, which can be explained by insufficient water in the formulation caused by the high concentration of solids. This phenomenon has been previously reported, with a decrease in thickening for the highest concentrations of added soy protein (Alvarez et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…3. This is an appropriate test for analyzing the gel character (G' > G") of samples, because as long as the strain amplitudes are below the limiting value (γ max ) the complex modulus (G*, measurement of the overall resistance (elastic and viscous)) pattern has a plateau value, indicating that the gel structure is stable under these conditions (Alvarez, Fernández, Olivares, & Canet, 2012). According to the authors just cited, γ max is defined as the strain above which G* decreases by more than 10% of the G* max value.…”
Section: Effect Of Hhp Treatment and Concentration On Mechanical Specmentioning
confidence: 99%
“…Additionally, the effect of soybean protein isolate (SPI), which contains 90% protein and usually used in the food industry (Zhu, Liu, Fu, & Zhao, 2016), on physicochemical, functional and sensory characteristics of MP products has been reported. Obtained results showed that SPI concentrations had a significant impact on rheological properties of MP (Álvarez, Fernández, Olivares, & Canet, 2012). The effect of whey protein concentrate, pectin, inulin and extra virgin olive oil to modify the rheological, thermal, structural properties and sensory quality of MP has also been studied (María Dolores Alvarez, Fernández, Olivares, & Canet, 2010;Conforti, Lupano, & Yamul, 2013).…”
Section: Introductionmentioning
confidence: 99%